WEB APPLICATION FOR PROCESSING IMAGES OF LARGE SIZE - O. N. Vinichuk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
It was developed the web application allowing to process large-volume images, affecting the minimum temporal characteristics. The flowcharts for implementing of the application logic are presented.